Neural response to errors is associated with problematic alcohol use over time in combat-exposed returning veterans: An event-related potential study. (1st February 2018) - Crane, Natania A.; Gorka, Stephanie M.; Burkhouse, Katie L.; Afshar, Kaveh; Greenstein, Justin E.; Aase, Darrin M.; Proescher, Eric; Schroth, Christopher; Kennedy, Amy E.; Phan, K. Luan
Highlights: We examined error-related negativity (ERN) and alcohol use in veterans over time. ERN magnitude was associated with problematic alcohol use over time. Veterans with a smaller ERN showed a decrease in problematic alcohol use over time. Veterans with a larger ERN had no change in problematic alcohol use over time. This disrupted brain error-related circuitry may be an important therapeutic target. Abstract: Background: Currently, we do not have biomarkers to help identify individuals at-risk for chronic, problematic alcohol use, especially among veteran populations, who have notoriously high rates of alcohol use. One biomarker that may predict individuals at risk for chronic, problematic alcohol use is error-related brain activity. We examined longitudinal associations between the error-related negativity (ERN), an event-related potential observed following the commission of errors, and problematic alcohol use among U.S. military veterans returning from recent conflicts in Iraq and Afghanistan. Methods: Forty-six military veterans, aged 18–55 years, completed a well-validated flanker task known to elicit the ERN at baseline. Problematic alcohol use and other clinically relevant variables were assessed at baseline, 3-, 6-, 9-, 12-, 15-, 18-, 21-months, and 2 years. Results: Results indicated that the ERN magnitude was associated with problematic alcohol use over time, even after controlling for relevant clinical variables. Specifically, veterans with a smaller ERN magnitude evidenced a decline in problematic alcohol use over time, while veterans with a larger ERN magnitude had no change in their problematic alcohol use across the follow-up. In addition, exploratory analyses found that treatment engagement during the study did not moderate these relationships. Conclusions: Our findings provide preliminary evidence that ERN can be used as a predictor of problematic alcohol use over time. Therefore, neural response to errors could help to identify individuals at risk for continued problematic alcohol use for intervention efforts and suggests that error processing may be an important therapeutic target within Alcohol Use Disorder intervention efforts.